2020
DOI: 10.3171/2020.2.spine191439
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the neuroprotective effects of ozone in an experimental spine injury model

Abstract: OBJECTIVEThe pathophysiology of spine injury consists of primary and secondary damage mechanisms. The vast majority of treatments aim to prevent or at least stop the progression of secondary neurotoxic events during the acute period. Ozone has been found to have potent antiinflammatory effects, to activate the immune system, and to have a substantial impact on the antioxidant system. In this study the authors aimed to evaluate the neuroprotective effects of ozone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Gürkan et al have described that Ozone was capable of reducing IL-1β, TNF-α and IL-6 in an experimental model of spine surgery. O3 was similar to Methylprednisolone, but the combination of both (O3 plus Methylprednisolone) was even more effective 26 . Zamora et al have observed that in a septic model of peritonitis, Ozone plus antibiotics decreased the expression of IL-1β 27 .…”
Section: Discussionmentioning
confidence: 90%
“…Gürkan et al have described that Ozone was capable of reducing IL-1β, TNF-α and IL-6 in an experimental model of spine surgery. O3 was similar to Methylprednisolone, but the combination of both (O3 plus Methylprednisolone) was even more effective 26 . Zamora et al have observed that in a septic model of peritonitis, Ozone plus antibiotics decreased the expression of IL-1β 27 .…”
Section: Discussionmentioning
confidence: 90%
“…Gürkan et al have described that Ozone was capable of reducing IL-1β, TNF-α and IL-6 in an experimental model of spine surgery. O 3 was similar to Methylprednisolone, but the combination of both (O 3 plus Methylprednisolone) was even more effective [30]. Zamora et al have observed that in a septic model of peritonitis, Ozone plus antibiotics decreased the expression of IL-1β [31].…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental setting regarding acute spinal injuries, ozone combined with steroid therapy seems to hasten clinical and to increase histological recovery compared with steroids alone. [ 5 ] Intralesional OT has been described for the treatment of subcutaneous swellings as lipomas: Kara recently reported a case of a 31-year-old woman, harboring a painful mass on the forearm which determined local pain and paresthesia, treated with local ozone injection. [ 6 ] This treatment determined the sudden disappearance of local pain and the reduction of tumor dimensions.…”
Section: Discussionmentioning
confidence: 99%